Method for preparing oxygen evolution electrode

The bottom layer and catalytic layer of the oxygen electrode analyzing the oxygen electrode on the mesh substrate through the vacuum sedimentation process solves the problem of low intensity and poor material stability in the existing technology, and realizes efficient and stable catalytic performance and electrolytic grooves. stability.

CN119372709AActive Publication Date: 2025-01-28SHANGHAI ZHIZHEN NEW ENERGY EQUIP CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411975592.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the prior art, the preparation of oxygen evolution electrodes mostly uses chemical immersion or electroplating processes, resulting in low bond strength, poor material stability, and significant catalytic performance attenuation.

Method used

The oxygen electrode of a vacuum sedimentation process is adopted, and the underlying and catalytic layer is formed by depositing targets on the mesh substrate. Combined with the protective gas and reaction gas indoor in the vacuum cavity, the deposition current and partial pressure are adjusted to form a porous catalytic layer.

Benefits of technology

It improves the film binding force and material stability of the oxygen electrode, enhances the catalytic performance, reduces the reaction of the potential, and improves the efficiency of hydrogen making and the stability of the electrolytic groove.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372709A_ABST
    Figure CN119372709A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water electrolysis hydrogen production, in particular to a method for preparing an oxygen evolution electrode. The preparation method comprises the following steps: selecting stainless steel and titanium nickel as a substrate net-shaped base material, and cleaning the net-shaped base material; the net-shaped base material and the target material are put into a vacuum chamber, protective gas and reaction gas are introduced into the vacuum chamber, deposition current and deposition bias voltage are applied, and the target material is adopted to deposit on the net-shaped base material to form a bottom layer; the deposition current is gradually increased, the deposition bias voltage is gradually reduced, the target material is deposited on the bottom layer to form a catalyst layer, and the oxygen evolution electrode is obtained; and moving the oxygen evolution electrode into the reaction chamber, and introducing a reaction medium into the reaction chamber to etch the catalyst layer, so that the catalyst layer has a porous network. The current and bias voltage are adjusted in the deposition process, the growth orientation of the catalytic material is adjusted, and a compact and intricate branch network is formed, so that the binding force between the catalytic layer and the net-shaped base material is improved, and meanwhile, the specific surface area of the oxygen evolution electrode is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of water electrolysis for hydrogen production technology, and in particular to a method for preparing an oxygen evolution electrode. Background Technology

[0002] Hydrogen energy can be widely used in methanol production, oil hydrogenation, ammonia synthesis, metal smelting, heating, and vehicle transportation. With the significant growth in total renewable energy volume, it will become one of the major energy sources. The cost of its power generation is continuously decreasing as technology matures and scales up, making renewable energy-based hydrogen production potentially competitive in the market.

[0003] Currently, the anodes in electrolyzers mainly use MEA (membrane electrode coating) technology, lacking a high-efficiency oxygen evolution electrode. Preparation often involves chemical immersion or electroplating, depositing a layer of nickel-iron material onto the porous diffusion layer surface. This results in low bonding strength, frequent powder shedding during short-term operation, and significant degradation of catalytic performance. Summary of the Invention

[0004] This application provides a method for preparing an oxygen evolution electrode, which aims to improve the film adhesion and material stability by using a vacuum deposition process.

[0005] This application provides a method for preparing an oxygen evolution electrode, the method comprising: S1: Clean the mesh substrate; S2: Place the mesh substrate and the target material into a vacuum chamber, and introduce protective gas and reactive gas into the vacuum chamber. Apply deposition current and deposition bias voltage, and use the target material to deposit an underlayer on the mesh substrate. S3: Gradually increase the deposition current and gradually decrease the deposition bias voltage, and use the target material to deposit a catalytic layer on the bottom layer to obtain the oxygen evolution electrode; S4: Move the oxygen evolution electrode into the reaction chamber, and introduce a reaction medium into the reaction chamber to etch the catalyst layer so that the catalyst layer has a porous network.

[0006] In one possible design, the material of the mesh substrate includes at least one of titanium mesh, stainless steel mesh, and nickel mesh.

[0007] In one possible design, in step S2, the protective gas and the reactive gas are O2 and Ar.

[0008] In one possible design, in step S2, the target material is deposited on the surface of the mesh substrate using a physical vapor deposition process or an electroplating impact process to form the underlayer.

[0009] In one possible design, the target material includes at least one of titanium target material, nickel target material, iron target material, nickel-iron alloy target material, stainless steel target material, and iron-cobalt alloy target material.

[0010] In one possible design, the underlying material includes one or more combinations of metals and their alloy oxides, such as nickel, titanium, and aluminum.

[0011] In one possible design, in step S3, the deposition current is gradually increased from 5A to 12A, and the deposition voltage is gradually decreased from 1500V to 120V.

[0012] In one possible design, in step S4, the reaction medium is H2, Ar, or an alkaline solution.

[0013] In one possible design, the main element of the catalyst layer is Ni-Fe-Ox, with Fe atoms accounting for 20%-40% of the total Ni-Fe atoms; The doping element of the catalyst layer includes at least one of Co, Mn, and Cr, and the proportion of the atoms of the doping element to the total atoms is 15%-30%.

[0014] In one possible design, the thickness of the oxygen evolution electrode is 300nm-500nm.

[0015] In one possible design, the specific surface area of ​​the oxygen evolution electrode is >100 m². 2 / g.

[0016] In one possible design, the surface contact angle of the oxygen evolution electrode is <40°.

[0017] In a second aspect, this application also provides an oxygen evolution electrode prepared by the method described above, wherein the oxygen evolution electrode comprises a mesh substrate, a bottom layer, and a catalyst layer in an integral structure.

[0018] In a third aspect, this application also provides an electrolytic cell comprising the oxygen evolution electrode described above.

[0019] It should be understood that the above general description and the following detailed description are merely exemplary and do not limit this application. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the process for preparing the oxygen evolution electrode provided in this application; Figure 2 A schematic cross-sectional view of the oxygen evolution electrode provided in this application; Figure 3 The scanning electron microscope image of the oxygen evolution electrode surface provided in this application; Figure 4 The experimental diagram provided in this application represents the hydrophilicity of the oxygen evolution electrode; Figure 5 A comparison diagram of polarity curves for Embodiment 1, Embodiment 4, and the comparative example (untreated porous diffusion layer) provided in this application; Figure 6 A schematic diagram showing the change of voltage over time required for the electrolysis of water in the electrolyzer provided in this application.

[0021] Figure label: 1-Oxygen evolution electrode; 11-Mesh substrate; 12-Bottom Layer; 13-Catalyst layer.

[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application. Detailed Implementation

[0023] To better understand the technical solution of this application, the embodiments of this application will be described in detail below with reference to the accompanying drawings.

[0024] It should be understood that the described embodiments are merely some, not all, of the embodiments in this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without inventive effort are within the scope of protection of this application.

[0025] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0026] It should be understood that the term "and / or" used in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this article generally indicates that the preceding and following related objects have an "or" relationship.

[0027] It should be noted that the directional terms such as "upper," "lower," "left," and "right" described in the embodiments of this application are used to describe the angles shown in the accompanying drawings and should not be construed as limiting the embodiments of this application. Furthermore, in the context, it should be understood that when it is mentioned that an element is connected "upper" or "lower" to another element, it can be directly connected to the other element "upper" or "lower," or indirectly connected to the other element "upper" or "lower" through an intermediate element.

[0028] With increasing global focus on environmental protection and decarbonization, and advancements in renewable energy power generation technologies, utilizing renewable energy sources such as wind, electricity, solar, photovoltaic, and hydropower to produce hydrogen is a crucial pathway to achieving a green hydrogen economy. Hydrogen energy can be widely applied in methanol production, oil hydrogenation, ammonia synthesis, metal smelting, heating, and vehicle transportation. The total growth rate of renewable energy is significant, making it one of the major energy sources. Its power generation costs are continuously decreasing as technology matures and scales up, making renewable energy-based hydrogen production potentially competitive in the market. Furthermore, renewable energy-based hydrogen production can absorb curtailed wind, solar, and hydropower, yielding low-cost hydrogen.

[0029] Hydrogen production technologies via water electrolysis include alkaline water electrolysis, proton exchange membrane (PEM) water electrolysis, alkaline anion exchange membrane (AEM) water electrolysis, and solid oxide water electrolysis.

[0030] Among them, alkaline water electrolysis for hydrogen production is the most mature technology. It has the advantages of low equipment cost, long life and robustness, and is suitable for large-scale production of green hydrogen. However, it has the disadvantages of low current density and high electrolysis energy consumption. In addition, due to the thick diaphragm in the alkaline electrolyzer, the resistance is relatively high, resulting in relatively low hydrogen production efficiency and low hydrogen purity. Therefore, de-alkali mist treatment is required to improve the hydrogen purity.

[0031] The proton exchange membrane in PEM water electrolysis for hydrogen production is very thin and has low resistance, allowing it to withstand large currents while maintaining high efficiency, thus resulting in high hydrogen production efficiency. However, PEM electrolyzers need to operate in a highly acidic and oxidizing environment, which places high demands on the materials used, particularly relying on expensive metals such as iridium, platinum, and titanium, leading to higher costs.

[0032] Alkaline luminescent (AEM) combines the advantages of traditional alkaline liquid electrolyte water electrolysis and PEM water electrolysis, allowing the use of non-precious metal catalysts in alkaline media, thus reducing equipment and material costs. However, AEM water electrolysis technology is still in the experimental stage, and the thermal and chemical stability of the oxygen evolution electrode is poor. Therefore, developing an AEM electrolytic cell anolyte and its preparation method is particularly important.

[0033] In AEM electrolyzers, the GDE (Gas diffusion electrode) and CCM (catalyst-coated membrane) approaches represent two distinct AEM preparation techniques. The CCM approach involves directly depositing the catalyst onto the ion exchange membrane to form a catalyst coating. This approach can be achieved through catalyst coating technology, where catalyst powder and ionomers are mixed with a suitable solvent and then directly coated onto the membrane. The preparation process is relatively complex, requiring precise control of the catalyst coating amount and uniformity, and the membrane stability may be affected by the catalyst deposition process. The GDE approach typically involves depositing the catalyst onto a gas diffusion layer (GDL) or a porous transport layer (PTL). The preparation process is relatively simple and easily scalable. Furthermore, the GDE approach optimizes the electrode structure, improving the uniform distribution and transport of the protective gas, thereby increasing the rate and efficiency of water electrolysis and enhancing the effective utilization of the catalyst.

[0034] Currently, most oxygen evolution electrode preparations employ chemical immersion or electroplating processes, where a layer of nickel-iron material is electroplated onto the surface of a porous diffusion layer. This process results in low bonding strength, frequent powder shedding during short-term operation, and significant degradation of catalytic performance.

[0035] The MEA scheme involves composite catalysts onto anion exchange membranes. However, the polymer membranes swell and shrink significantly in alkaline environments, making the catalysts prone to detachment and resulting in noticeable performance degradation.

[0036] Compared with the conventional oxygen evolution electrode and the MEA scheme, the contact resistance between the membrane and the catalyst is increased, the ohmic internal resistance is significantly increased, and the overall performance is significantly degraded.

[0037] The oxygen evolution electrode was fabricated without hydrophilicity / hydrophobicity adjustment on its surface to construct a stable gas-solid-liquid three-phase interface, thus suppressing electrolyte overflow and gas transport issues under high current density.

[0038] Therefore, this embodiment provides a method for preparing an oxygen evolution electrode to solve the above-mentioned technical problems.

[0039] like Figure 1 The diagram shows a process flow chart for preparing an oxygen evolution electrode. The preparation method includes: S1: Select the mesh substrate 11 and clean the mesh substrate 11; S2: Place the mesh substrate 11 and the target material into the vacuum chamber, and introduce protective gas and reactive gas into the vacuum chamber. Apply deposition current and deposition bias voltage, and use the target material to deposit the bottom layer 12 on the mesh substrate 11. S3: Gradually increase the deposition current and gradually decrease the deposition bias voltage, and use the target material to deposit a catalyst layer 13 on the bottom layer 12 to obtain the oxygen evolution electrode 1; S4: Move the oxygen evolution electrode 1 into the reaction chamber, and introduce a reaction medium into the reaction chamber to etch the catalyst layer so that the catalyst layer 13 has a porous network.

[0040] Specifically, the material of the mesh substrate 11 includes at least one of titanium mesh, stainless steel mesh, and nickel mesh. The mesh substrate can also be made of other materials, depending on the actual situation; this embodiment does not limit this. Before placing the mesh substrate 11 into the vacuum chamber, the mesh substrate 11 can be cleaned. For example, the mesh substrate 11 can be ultrasonically cleaned in ethanol and water to remove grease and debris from its surface.

[0041] Then, the mesh substrate 11 is placed inside the vacuum chamber, and the target material is placed inside the vacuum chamber, with the distance between the target material and the mesh substrate 11 set between 4cm and 8cm. The target material includes at least one of titanium, nickel, iron, nickel-iron alloy, stainless steel, and iron-cobalt alloy. Alternatively, other materials can be used for the target material, depending on the specific circumstances; this embodiment does not impose such limitations.

[0042] A reactant gas and a protective gas, such as Ar and O2, are introduced into the vacuum chamber to allow the target material to react with oxygen to generate oxides. Other gases can also be used as the protective gas, depending on the specific circumstances; this embodiment does not impose any limitations on this.

[0043] The target material is deposited on the surface of the mesh substrate 11 to form the bottom layer 12 using physical vapor deposition (PVD) or electroplating impact processes. PVD processes include, but are not limited to, magnetron sputtering, evaporation, and multi-arc ion plating.

[0044] Taking magnetron sputtering as an example, during the magnetron sputtering process, electrons fly towards the mesh substrate 11 under the influence of an electric field. During this process, electrons collide with argon atoms, ionizing them to generate argon ions and new electrons. The new electrons fly towards the mesh substrate 11 under the influence of the electric field, while the argon ions fly towards the target material and bombard its surface with high energy, causing sputtering. Atoms or molecules on the target surface detach and deposit onto the surface of the mesh substrate 11, forming the bottom layer 12. The bottom layer 12 is made of materials including, but not limited to, metals and their alloy oxides such as nickel, titanium, and aluminum, and may be one or more combinations thereof.

[0045] Specifically, before depositing the bottom layer 12, the vacuum chamber can be evacuated to 5°C. 10 ﹣3The heater was turned on and heated to 300°C, held for a period of time, and then Ar and O2 were introduced into the vacuum chamber. The sputtering pressure was controlled at 2 Pa. At the deposition temperature of 300°C, the deposition current was controlled at 5 A, the deposition time at 10 min, and the deposition bias at 1500 V, resulting in a metal underlayer 12.

[0046] Deposition continues on the bottom layer 12, with the deposition current gradually increased and the deposition bias gradually decreased. A catalytic layer 13 is formed on the bottom layer 12 using a target material, resulting in the oxygen evolution electrode 1. For example, the deposition current can be gradually increased from 5A to 12A, and the deposition bias can be gradually decreased from 1500V to 120V. With the increase in deposition current and the decrease in deposition voltage, the mechanical properties such as deposition rate and film hardness are improved to a certain extent. In this embodiment, by adjusting the current and bias during the deposition process, the growth orientation of the catalytic material is adjusted to form a dense and intricately branched network, thereby improving the bonding force between the catalytic layer 13 and the mesh substrate 11, and also increasing the specific surface area of ​​the oxygen evolution electrode 1.

[0047] Of course, in this step, when different target materials are used, the applied deposition current, deposition voltage and deposition time will be different, and the resulting oxygen evolution electrode 1 (containing different elements) will also be different.

[0048] For example, during the deposition of the catalyst layer 13 on the bottom layer 12, when titanium or nickel-iron alloy targets are selected, the deposition current is controlled at 5A, the deposition time at 10min, and the deposition bias at 1200V at a deposition temperature of 300℃. Then, at a deposition temperature of 300℃, the deposition current is controlled at 10A, the deposition time at 30min, and the deposition bias at 500V. Finally, at a deposition temperature of 300℃, the deposition current can be controlled at 10A, the deposition time at 30min, and the deposition bias at 500V. After deposition is completed, the vacuum chamber is gradually cooled to room temperature to obtain the oxygen evolution electrode 1Ni-Fe-Ox electrode.

[0049] Alternatively, during the deposition of the catalyst layer 13 on the bottom layer 12, when titanium, nickel, and iron targets are selected, the deposition current is controlled at 5 A for the nickel target and 3 A for the iron target at a deposition temperature of 300°C, the deposition time is 15 min, and the deposition bias is 1200 V. At the same deposition temperature, the deposition current is controlled at 10 A for the nickel target and 3 A for the iron target, the deposition time is 30 min, and the deposition bias is 500 V. At the same deposition temperature, the deposition current is controlled at 12 A for the nickel target and 3 A for the iron target, the deposition time is 45 min, and the deposition bias is 120 V. After deposition, the vacuum chamber is gradually cooled to room temperature to obtain the oxygen evolution electrode 1 (Ni-Fe-Ox electrode).

[0050] Alternatively, during the deposition of the catalyst layer 13 on the bottom layer 12, when nickel and stainless steel (316L) targets are selected, the deposition current is controlled at 5 A for the nickel target and 2 A for the stainless steel target at a deposition temperature of 300°C, the deposition time is 10 min, and the deposition bias is 1500 V. At the same deposition temperature, the deposition current is controlled at 10 A for the nickel target and 3 A for the stainless steel target at a deposition temperature of 30°C, the deposition time is 30 min, and the deposition bias is 500 V. At the same deposition temperature, the deposition current is controlled at 12 A for the nickel target and 4 A for the stainless steel target at a deposition temperature of 30°C, the deposition time is 40 min, and the deposition bias is 120 V. After deposition, the vacuum chamber is gradually cooled to room temperature to obtain the oxygen evolution electrode 1 (Ni-Fe-Cr-Ox electrode).

[0051] Alternatively, during the deposition of the catalyst layer 13 on the bottom layer 12, when nickel and iron-cobalt alloy targets are selected, the deposition current is controlled at 5 A for the nickel target and 2 A for the iron-cobalt alloy target at a deposition temperature of 300°C, the deposition time is 10 min, and the deposition bias voltage is 1500 V. At the same deposition temperature, the deposition current is controlled at 10 A for the nickel target and 3 A for the iron-cobalt alloy target at 30°C, the deposition time is 30 min, and the deposition bias voltage is 500 V. At the same deposition temperature, the deposition current is controlled at 12 A for the nickel target and 4 A for the iron-cobalt alloy target at 30°C, the deposition time is 40 min, and the deposition bias voltage is 120 V. After deposition, the vacuum chamber is gradually cooled to room temperature to obtain the oxygen evolution electrode 1 (Ni-Fe-Co-Ox electrode).

[0052] The thickness of the oxygen evolution electrode 1 can be 300nm-500nm. For example, the thickness of the oxygen evolution electrode 1 can be 300nm, 400nm, 500nm, etc., or the thickness can be further increased or decreased according to the needs. The specific thickness can be set according to the actual situation, and this embodiment does not limit it.

[0053] The obtained oxygen evolution electrode 1 is transferred to the reaction chamber, and the catalyst layer 13 is etched through the reaction medium in the reaction chamber to make it porous, thereby increasing the specific surface area of ​​the oxygen evolution electrode 1. Please refer to [reference needed] for details. Figure 2 Figure 2 shows a cross-sectional schematic diagram of the oxygen evolution electrode 1.

[0054] like Figure 3 The image shown is a scanning electron microscope image of the surface of oxygen evolution electrode 1. It can be seen that the surface of oxygen evolution electrode 1 has a porous structure, which gives oxygen evolution electrode 1 a high specific surface area.

[0055] In some embodiments, the reaction medium may be H2, Ar, or an alkaline solution.

[0056] For example, the reaction chamber can be a vacuum environment. After the oxygen evolution electrode 1 is moved to the reaction chamber, the reaction chamber is evacuated to 5°C. 10 ﹣3The reaction chamber was heated to 600°C and held at that temperature for a period of time. Subsequently, H2 was introduced into the reaction chamber, the vacuum was maintained at 0.2 Pa, the deposition bias was controlled at 800V-1200V, and the processing time was 60 minutes at the deposition temperature of 600°C.

[0057] Alternatively, the reaction chamber can be a vacuum environment. After moving the oxygen evolution electrode 1 into the reaction chamber, the reaction chamber is evacuated to 5°C. 10 ﹣3 The reaction chamber was heated to 800°C and held at that temperature for a period of time. Then, argon gas was introduced into the reaction chamber, the vacuum was maintained at 0.01 Pa, the deposition bias was controlled at 1000 V, and the processing time was 30 min at the deposition temperature of 800°C.

[0058] Alternatively, 0.1M potassium hydroxide can be placed in the reaction chamber. After moving oxygen evolution electrode 1 to the reaction chamber, the potassium hydroxide can be heated to 120°C for 30 minutes. After completion, it can be removed and dried.

[0059] In this embodiment, the oxygen evolution electrode 1 obtained by the above preparation method can achieve stable adhesion of the catalyst on the substrate surface of the oxygen evolution electrode 1, thereby improving the stability of the oxygen evolution electrode 1. Simultaneously, the above preparation method endows the oxygen evolution electrode 1 with a hydrophilic surface and porous structure, greatly enhancing the enrichment of reactants on the catalyst surface to generate the reaction, significantly reducing the reaction overpotential, and improving catalytic performance. Furthermore, the above preparation method is simple, cost-effective, and easy to mass-produce the oxygen evolution electrode 1.

[0060] In some embodiments, the oxygen evolution electrode 1 obtained by the above preparation method has a specific surface area > 100 m². 2 / g, which makes oxygen evolution electrode 1 a porous structure, improves catalytic efficiency. In some embodiments, the oxygen evolution electrode 1 obtained by the above preparation method has a surface contact angle of <40°, which improves the hydrophilicity of the oxygen evolution electrode 1, realizes the gas-solid-liquid three-phase interface, and stabilizes the entry of reactants and the discharge of gas.

[0061] Please refer to Figure 4 , Figure 4 The diagram illustrates the hydrophilicity of the oxygen evolution electrode 1 in this embodiment. It shows a liquid droplet falling onto the test surface (the surface of the oxygen evolution electrode 1) to measure the contact angle of the liquid on the test surface. When the contact angle (CA) is 90° or higher, the test surface is hydrophobic; when the contact angle (CA) is less than 90°, the test surface is hydrophilic.

[0062] As can be seen, the contact angle (CA) in this experiment was 22.518°, indicating that the test surface (the surface of oxygen evolution electrode 1) has good hydrophilicity.

[0063] In some embodiments, the main element of the catalyst layer 13 is Ni-Fe-Ox, and the proportion of Fe atoms to the total Ni-Fe atoms is 20%-40%. The doping element of the catalyst layer 13 includes at least one of Co, Mn, and Cr, and the proportion of the doping element atoms to the total atoms is 15%-30%.

[0064] In this embodiment, by limiting the ratio of Fe atoms in the catalyst layer 13, the overpotential of the oxygen evolution electrode 1 is reduced, thereby improving catalytic performance, reaction rate and efficiency. This results in a lower actual voltage required for the relative current density, less energy consumption, and higher catalytic activity.

[0065] Based on the above, the possible preparation methods of the oxygen evolution electrode 1 will be described in detail below in this embodiment.

[0066] In one embodiment (Example 1), a stainless steel mesh of uniform thickness is selected as the mesh substrate 11, and the stainless steel mesh is ultrasonically cleaned in ethanol and water to remove surface grease and surface debris.

[0067] Secure the stainless steel mesh to the hanger and move it into the vacuum chamber. When the vacuum reaches 5... 10 ﹣3 At 300°C, the heater was turned on and heated to 300°C, and held at that temperature for a period of time. Then, Ar and O2 were introduced into the vacuum chamber. Simultaneously, titanium and nickel-iron alloy targets were placed in the vacuum chamber, and the sputtering pressure was controlled at 2 Pa. At a deposition temperature of 300°C, the deposition current was controlled at 5 A, the deposition time at 10 min, and the deposition bias at 1500 V, resulting in a titanium underlayer 12.

[0068] The catalyst layer 13 was deposited on the bottom layer 12. At a deposition temperature of 300℃, the deposition current for the titanium and nickel-iron alloy targets was controlled at 5A, the deposition time at 10min, and the deposition bias voltage at 1200V. Then, at the same deposition temperature, the deposition current for the titanium and nickel-iron alloy targets was controlled at 10A, the deposition time at 30min, and the deposition bias voltage at 500V. Finally, at the same deposition temperature, the deposition current for the titanium and nickel-iron alloy targets could be controlled at 10A, the deposition time at 30min, and the deposition bias voltage at 500V. After deposition, the vacuum chamber was gradually cooled to room temperature to obtain the oxygen evolution electrode 1, a Ni-Fe-Ox electrode with a thickness of 300nm.

[0069] After moving oxygen evolution electrode 1 to the reaction chamber, the reaction chamber is evacuated to 5°C. 10 ﹣3The reaction chamber was heated to 600°C and held at that temperature for a period of time. Subsequently, H2 was introduced into the reaction chamber, the vacuum was maintained at 0.2 Pa, the deposition bias was controlled at 800V-1200V, and the processing time was 60 minutes at the deposition temperature of 600°C.

[0070] In another embodiment (Example 2), a nickel mesh of uniform thickness is selected as the mesh substrate 11. The nickel mesh is placed in ethanol and water for ultrasonic cleaning to remove surface grease and surface debris.

[0071] Fix the nickel mesh onto the electrode clamp, move it to the vacuum chamber, and evacuate the chamber until the vacuum reaches 5%. At 10⁻³ Pa, the heater was turned on to heat to 300°C and held for a period of time. Then, Ar and O₂ were introduced into the vacuum chamber. Simultaneously, titanium, nickel, and iron sputtering targets were placed in the vacuum chamber, and the sputtering pressure was controlled at 2 Pa. At a deposition temperature of 300°C, the deposition current was controlled at 5 A, the deposition time at 10 min, and the deposition bias at 1500 V, resulting in a titanium underlayer 12.

[0072] Continue depositing the catalyst layer 13 on the bottom layer 12. At a deposition temperature of 300℃, control the deposition current to be 5 A for the nickel target and 3 A for the iron target, the deposition time to be 15 min, and the deposition bias voltage to be 1200 V. At the same deposition temperature of 300℃, control the deposition current to be 10 A for the nickel target and 3 A for the iron target, the deposition time to be 30 min, and the deposition bias voltage to be 500 V. At the same deposition temperature of 300℃, control the deposition current to be 12 A for the nickel target and 3 A for the iron target, the deposition time to be 45 min, and the deposition bias voltage to be 120 V. After deposition, gradually cool the vacuum chamber to room temperature to obtain the oxygen evolution electrode 1, an oxygen Ni-Fe-Ox electrode with a diameter of 500 nm.

[0073] After moving oxygen evolution electrode 1 to the reaction chamber, the reaction chamber is evacuated to 5°C. 10 ﹣3 The reaction chamber was heated to 600°C and held at that temperature for a period of time. Subsequently, H2 was introduced into the reaction chamber, the vacuum was maintained at 0.2 Pa, the deposition bias was controlled at 800V-1200V, and the processing time was 60 minutes at the deposition temperature of 600°C.

[0074] In another embodiment (Example 3), a nickel mesh of uniform thickness is selected as the mesh substrate 11. The nickel mesh is placed in ethanol and water for ultrasonic cleaning to remove surface grease and surface debris.

[0075] Fix the nickel mesh onto the electrode clamp, move it to the vacuum chamber, and evacuate the chamber until the vacuum reaches 5%. At 10⁻³ Pa, the heater was turned on to heat to 300°C and held for a period of time. Then, Ar and O₂ were introduced into the vacuum chamber. Simultaneously, nickel and 316L stainless steel targets were placed in the vacuum chamber, and the sputtering pressure was controlled at 2 Pa. At a deposition temperature of 300°C, the deposition current was controlled at 5 A, the deposition time at 10 min, and the deposition bias at 1500 V, resulting in a titanium underlayer 12.

[0076] The catalyst layer 13 was deposited on the bottom layer 12. At a deposition temperature of 300℃, the deposition current was controlled at 5 A for the nickel target and 2 A for the stainless steel target, with a deposition time of 10 min and a deposition bias of 1500 V. At the same deposition temperature, the deposition current was controlled at 10 A for the nickel target and 3 A for the stainless steel target, with a deposition time of 30 min and a deposition bias of 500 V. At the same deposition temperature, the deposition current was controlled at 12 A for the nickel target and 4 A for the stainless steel target, with a deposition time of 40 min and a deposition bias of 120 V. After deposition, the vacuum chamber was gradually cooled to room temperature to obtain the oxygen evolution electrode 1 (Ni-Fe-Cr-Ox electrode), with a thickness of 500 nm.

[0077] The reaction chamber can be a vacuum environment. After moving the oxygen evolution electrode 1 into the reaction chamber, the reaction chamber is evacuated to 5°C. 10 ﹣3 The reaction chamber was heated to 800°C and held at that temperature for a period of time. Then, argon gas was introduced into the reaction chamber, the vacuum was maintained at 0.01 Pa, the deposition bias was controlled at 1000 V, and the processing time was 30 min at the deposition temperature of 800°C.

[0078] In another embodiment (Example 4), a nickel mesh of uniform thickness is selected as the mesh substrate 11. The nickel mesh is placed in ethanol and water for ultrasonic cleaning to remove surface grease and surface debris.

[0079] Secure the nickel mesh to the electrode clamp, move it to the vacuum chamber, and evacuate the chamber until the vacuum reaches 5* At 10⁻³ Pa, the heater was turned on to heat to 300°C and held for a period of time. Then, Ar and O₂ were introduced into the vacuum chamber. Simultaneously, nickel and iron-cobalt alloy targets were placed in the vacuum chamber, and the sputtering pressure was controlled at 2 Pa. At a deposition temperature of 300°C, the deposition current was controlled at 5 A, the deposition time at 10 min, and the deposition bias at 1500 V, resulting in a titanium underlayer 12.

[0080] Continuing with the deposition of the catalyst layer 13 on the bottom layer 12, the deposition temperature was maintained at 300℃, with a deposition current of 5A for the nickel target and 2A for the iron-cobalt alloy target, a deposition time of 10 min, and a deposition bias of 1500V. At the same deposition temperature, the deposition current was maintained at 300℃, with a nickel target of 10A and 3A for the iron-cobalt alloy target, a deposition time of 30 min, and a deposition bias of 500V. At the same deposition temperature, the deposition current was maintained at 12A for the nickel target and 4A for the iron-cobalt alloy target, a deposition time of 40 min, and a deposition bias of 120V. After deposition, the vacuum chamber was gradually cooled to room temperature to obtain the oxygen evolution electrode 1 (Ni-Fe-Co-Ox electrode).

[0081] The oxygen evolution electrode 1 was moved to the reaction chamber, which contained 0.1M potassium hydroxide. After moving the oxygen evolution electrode 1 to the reaction chamber, the potassium hydroxide was heated to 120°C for 30 minutes. After the process was completed, the electrode was removed and dried.

[0082] This embodiment also provides an oxygen evolution electrode 1, which is prepared by the method described above, and will not be repeated here. Please refer to [link to previous document]. Figure 2 The oxygen evolution electrode 1 includes a mesh substrate 11, a bottom layer 12, and a catalyst layer 13, all of which are integrally formed. The mesh substrate 11 serves as a diffusion layer. In this embodiment, the bottom layer and the catalyst layer of the oxygen evolution electrode 1 are deposited on the surface of the diffusion layer using a vacuum deposition process, resulting in an integral structure between the diffusion layer and the catalyst layer 13.

[0083] This embodiment also provides an electrolyzer, which includes an oxygen evolution electrode 1, an exchange membrane, and a hydrogen evolution electrode stacked together. The hydrogen evolution electrode can be prepared as described above, and will not be repeated here. The electrolyzer can be used to electrolyze the electrolyte in the electrolyzer to produce hydrogen and oxygen.

[0084] In some embodiments, the electrolyte in the electrolytic cell can be an alkaline solution or pure water. Water molecules in the electrolyte undergo oxygen evolution reaction and hydrogen evolution reaction at the oxygen evolution electrode 1 and hydrogen evolution electrode, respectively, thereby decomposing into hydrogen and oxygen.

[0085] Since the catalyst layer 13 on the oxygen evolution electrode 1 in this embodiment is deposited on the surface of the diffusion layer by vacuum deposition, the catalyst layer 13 can be stably attached to the diffusion layer during the oxygen evolution reaction and is not easy to fall off, thereby improving the stability of the electrolyzer.

[0086] Please refer to the details. Figure 5 , Figure 5 The graph shows a comparison of polarity curves for Embodiments 1 and 4 above, as well as a comparative example (without a treated porous diffusion layer), illustrating the relationship between current density and voltage in the electrolytic cell. At the same current density, a lower voltage indicates lower output power, and thus better oxygen evolution performance of the oxygen evolution electrode 1.

[0087] from Figure 5 As can be seen, under the same current density, the voltage of the oxygen evolution electrode 1 prepared in Examples 1 and 4 is significantly lower than that of the oxygen evolution electrode 1 prepared in the comparative example. Therefore, the oxygen evolution electrode 1 prepared in this example has superior oxygen evolution performance.

[0088] Figure 6 This diagram illustrates the change in voltage over time required for water electrolysis in the electrolyzer of this embodiment. From... Figure 6 It can be seen that the voltage required for water electrolysis in the electrolyzer assembled with the oxygen evolution electrode 1 prepared in this embodiment does not fluctuate significantly and is stable, indicating that the electrolyzer has stable electrolysis performance, good alkali resistance and durability, and can maintain stable operation for a long time. This demonstrates that the oxygen evolution electrode 1 prepared in this embodiment has excellent stability.

[0089] Therefore, the preparation method of this application can be used to prepare oxygen evolution electrode 1 with high activity and high stability, and the preparation process is simple. Compared with the preparation of electrodes by chemical plating or electroplating, it reduces the risk of wastewater pollution to the environment.

[0090] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing an oxygen evolution electrode, characterized in that: The preparation method comprises: Placing a mesh substrate (11) and a target material into a vacuum chamber, introducing a protective gas and a reaction gas into the vacuum chamber, applying a deposition current and a deposition bias voltage, and using the target material to deposit on the mesh substrate (11) to form a bottom layer (12); Gradually increasing the deposition current and gradually decreasing the deposition bias voltage, using the target material to deposit on the bottom layer (12) to form a catalytic layer (13), thereby obtaining the oxygen evolution electrode (1); The oxygen evolution electrode (1) is moved into a reaction chamber, and a reaction medium is introduced into the reaction chamber to etch the catalyst layer, so that the catalyst layer (13) has a porous network.

2. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The material of the mesh substrate (11) includes at least one of a titanium mesh, a stainless steel mesh, and a nickel mesh.

3. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The protective gas and reaction gas are O2 and Ar.

4. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: When a target material is deposited on the mesh substrate (11) to form a bottom layer (12), the method specifically comprises: using a physical vapor deposition process or an electroplating impact process to deposit the target material on the surface of the mesh substrate (11) to form the bottom layer (12).

5. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The target material includes at least one of a titanium target material, a nickel target material, an iron target material, a nickel-iron alloy target material, a stainless steel target material, and an iron-cobalt alloy target material.

6. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The material of the bottom layer (12) includes one or more combinations of metals of nickel, titanium, aluminum and alloy oxide materials thereof.

7. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: When the deposition current is gradually increased and the deposition bias voltage is gradually decreased, the target material is used to deposit a catalytic layer (13) on the bottom layer (12) to obtain the oxygen evolution electrode (1), the deposition current is gradually increased from 5A to 12A, and the deposition voltage is gradually decreased from 1500V to 120V.

8. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The reaction medium is H2 or Ar or an alkaline solution.

9. The method for preparing an oxygen evolution electrode according to any one of claims 1 to 8, characterized in that: The main element of the catalyst layer (13) is Ni-Fe-Ox, and the ratio of Fe atoms to the total Ni-Fe atoms is 20%-40%; The doping element of the catalytic layer (13) includes at least one of Co, Mn and Cr, and the proportion of atoms of the doping element to total atoms is 15%-30%.

10. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The thickness of the oxygen evolution electrode (1) is 300nm-500nm.

11. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The specific surface area of ​​the oxygen evolution electrode (1) is greater than 100 m 2 / g.

12. The method for preparing an oxygen evolution electrode according to claim 1, characterized in that: The surface contact angle of the oxygen evolution electrode (1) is less than 40°.

Citation Information

Patent Citations

  • High-performance oxygen evolution electrode and preparation method thereof

    CN116590733A

  • Gas diffusion layer with pore structure, surface modification method and application

    CN117051424A

  • Porous catalyst gas diffusion electrode magnetron sputtering preparation method and electrode

    CN117418205A

  • Oxygen evolution electrode material and preparation method and application thereof

    CN117488357A

  • Nickel-iron layered double hydroxide-loaded oxygen evolution electrode and preparation method thereof

    CN117568847A